Organizational knowledge transfer: creating new knowledge from old knowledge - Moura, Rui; Dias, Álvaro; Quintas, Célia; Costa, Dilar (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The definition of knowledge supported by Nonakae Takeuchi (1995) considers that it is a human process that allows justifying personal belief about the truth. The individual is an integral part and is inseparable from knowledge. The authors also distinguish explicit knowledge, which can be expressed in words and numbers, and tacit knowledge, that is held by the individual in the form of know-how, and can be identified through their habits, behaviors, emotions, values and ideas. However, there is a wealth of professional knowledge in qualified people that are apart from active life voluntarily or involuntarily, through unemployment or retirement. This source of knowledge could be (re)transformed into new sources of competitiveness for organizations. In this context, this paper seeks to present the results of an exploratory study, orientated to identify knowledge transfer processes, from pensioners and long-term unemployed, to business professionals and companies, through the adaptation of mentoring programs. Five thematic areas of knowledge transfer were considered and selected as key areas of organizational competitiveness: Entrepreneurship, Innovation, Cooperation, Distribution, and Exportation. We consider this work relevant to the extent that the processes of change, caused by world crisis, tend to split fundamental knowledge that must be preserved. With the emergence of the knowledge society, we face problems, uncertainties and challenges arising not only from the financial crises and economic recessions, but also from the social transformations that we have seen in the processes of globalization, demographic change, technological revolution and the single currency, among others. The various transformations mentioned have produced paradoxical impacts, in particular job and knowledge management and the organization of work and working time. Such changes imply that researchers find new ways to a more holistic and human-centered organization. To realize our study we constructed a methodology of knowledge transfer, largely inspired by the work of Peet, Walsh, Rawak & Sober (2010). Our methodology comprised several steps: ( a) identify the knowledge, ( b ) access to persons owning knowledge, ( c ) integrating knowledge in projects, ( d ) combine ideas and initiatives, (e ) relaying knowledge, ( f ) enhance and apply knowledge. The experiential processes developed under this study give companies a large potential to be able to achieve their change objectives, incorporate new knowledge and increase their competitiveness. In this vein, we concluded that our methodology of knowledge transfer was effective as a mean for learning and to operationalize the knowledge held by mentors in strategic areas in the field of entrepreneurship, innovation and cooperation. We also concluded, by the duration of the project and through the measurement of the effects of knowledge transfer and its return in terms of effective improvement of business competitiveness, that it must be applied on a time scale projected in the medium and long term.